Analisis Pengaruh Perceived Organizational Support dan Loyalitas Karyawan Terhadap Kinerja Karyawan Rsu Martha Friska Multatuli - Devi Aprilia Lubis; Hilma Harmen (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the influence of Perceived Organizational Support and employee loyalty on employee performance at RSU Martha Friska Multatuli. Perceived Organizational Support refers to employees’ perception of how much the organization values their contributions and cares about their well-being. Employee loyalty reflects dedication and emotional attachment to the organization, demonstrated through responsibility, compliance, and commitment to contribute positively. This research uses a quantitative approach with path analysis. The sample consists of 69 contract employees from the nursing and medical support divisions, selected from a total population of 227 employees. The results show that Perceived Organizational Support and employee loyalty have a positive and significant effect on performance. Moreover, Perceived Organizational Support also significantly influences loyalty, and indirectly affects performance through employee loyalty.